1970
DOI: 10.1139/m70-117
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nitrogenase synthesis by Klebsiella pneumoniae

Abstract: PARUKO, R. A., and P. W. WILSON. 1970. Regulation of nitrogenase synthesis by Klebsiellapr~e~irrroniae.Can. J. Microbial. 16: 681-685. The synthesis of the nitrogenase system in Nz-fixing bacteria is repressed when the organisms are grown on NH4+-N. It has not been unequivocally determined, however, if N2 is necessary for induction in NH4+-deficient cultures. Previous experiments with Klebsiella ptre~itr~ot~iae, Azotohacter vinelandii, Closrridium pasteuriatzllm, and Rl~odospirillvm r~rbrlim have been inconclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

1971
1971
1980
1980

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 1 publication
1
22
0
Order By: Relevance
“…Ammonium ions stimulate cell-free amino acid incorporation (Lubin & Ennis, 1964) ; high NH$ concentrations are required for ribosomal stability in vitro (Hartman, Nolan & Amaya, 1971) and for the peptidyl transferase reaction (Miskin, Zamir & Elson, 1970). Under argon, only a limited amount of nitrogenase was derepressed, as previously observed by Parejko & Wilson, 1970; Casamino acids added prior to derepression increased the final activity obtained in one instance. Klebsiella pneumoniae, therefore, did not synthesize nitrogenase completely when only endogenous nitrogen sources were available.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Ammonium ions stimulate cell-free amino acid incorporation (Lubin & Ennis, 1964) ; high NH$ concentrations are required for ribosomal stability in vitro (Hartman, Nolan & Amaya, 1971) and for the peptidyl transferase reaction (Miskin, Zamir & Elson, 1970). Under argon, only a limited amount of nitrogenase was derepressed, as previously observed by Parejko & Wilson, 1970; Casamino acids added prior to derepression increased the final activity obtained in one instance. Klebsiella pneumoniae, therefore, did not synthesize nitrogenase completely when only endogenous nitrogen sources were available.…”
Section: Discussionmentioning
confidence: 60%
“…These include glutamine in Klebsiella pneumoniae (Parejko & Wilson, 1970), aspargine (Wilson, Hull & Burris, 1943;St John & Brill, 1972), urea (Wilson et al 1943;Hardy & Knight, 1967) and nitrate (Wilson et al 1943;Drozd et al 1972) in Azotobacter. This diversity suggests that a common intermediate, the most obvious being NH,+, is the effector of repression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magasanik and his co-workers (Tyler et al, 1974) demonstrated, using a cell-free transcription system, that unadenylylated glutamine synthetase activates the expression of the histidine utilization genes. Glutamine synthetase was also postulated to play an important role in the control of the utilization of alternative nitrogen sources, including N2, that are subject to repression by NH4+ (Shanmugam & Valentine, 1975;Magasanik, 1976).In Klebsiella pneumoniae, glutamine and glutamate play an important role in controlling nitrogenase biosynthesis (Parejko & Wilson, 1970;Shanmugam & Morandi, 1976), but the precise biochemical nature of this control is still unknown. To understand this process, we have sought for and isolated a pleiotropic, thermosensitive mutant strain of K. pneumonide.…”
mentioning
confidence: 99%